2007
DOI: 10.1002/bmc.949
|View full text |Cite
|
Sign up to set email alerts
|

Selective and sensitive determination of bis(7)‐tacrine, a high erythrocyte binding acetylcholinesterase inhibitor, in rat plasma by high‐performance liquid chromatography–tandem mass spectrometry

Abstract: The current study aims to develop a specific and sensitive LC-MS/MS method for determination of bis(7)-tacrine (B7T) in rat plasma. A 100 microL plasma sample was extracted with ethyl acetate. B7T and the internal standard (IS), pimozide, in the samples were then analyzed with LC-MS/MS in positive electrospray ionization condition. Chromatographic separation of B7T and IS was achieved in a C(18) reversed-phase HPLC column (150 x 2.1 mm i.d.) by isocratic elution with a mobile phase consisting of 0.05% formic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The pharmacokinetic research in the body of the rat showed that bis(7)-tacrine was rapidly and widely distributed to its target tissues such as brain[41,42]. In a model of acute focal cerebral ischemic insults in MCAO rats, bis(7)-tacrine at doses of 0.1 mg/kg and 0.2 mg/kg significantly reduced ischemic impairment in vivo[23].…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacokinetic research in the body of the rat showed that bis(7)-tacrine was rapidly and widely distributed to its target tissues such as brain[41,42]. In a model of acute focal cerebral ischemic insults in MCAO rats, bis(7)-tacrine at doses of 0.1 mg/kg and 0.2 mg/kg significantly reduced ischemic impairment in vivo[23].…”
Section: Discussionmentioning
confidence: 99%
“…LC/MS spectrometry based techniques are now the mainstay for such pharmacokinetic studies because of sensitivity, selectivity, speed, and cost effectiveness [9]. HPLC-MS/MS method for quantification of tacrine in biological samples has been developed [10]. However, we do not find HPLC-MS/MS methods reported in the literature for quantification of amiridine in biological samples.…”
Section: Introductionmentioning
confidence: 97%